2022
DOI: 10.1002/ps.7174
|View full text |Cite
|
Sign up to set email alerts
|

The dual impacts of specialized agricultural services on pesticide application intensity: Evidence from China

Abstract: BACKGROUND: Specialized agricultural services are a new trend in agricultural production around the world, especially in developing countries. However, the growing impacts of specialized agricultural services on pesticide application intensity are unclear. In regions facing pesticide overuse, do specialized agricultural services exacerbate or mitigate the problem? RESULTS: Based on province-level panel data from China from 2004 to 2018, this study examines the impact of specialized agricultural services on pes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Thus, Hypothesis 1 has been validated. Moreover, specialized agricultural services have a negative impact on pesticide application intensity ( 28 ). Femenia et al found that pesticide taxes appear to result in a significant reduction in pesticide use but require support for technological advancements to improve low-input cropping practices ( 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, Hypothesis 1 has been validated. Moreover, specialized agricultural services have a negative impact on pesticide application intensity ( 28 ). Femenia et al found that pesticide taxes appear to result in a significant reduction in pesticide use but require support for technological advancements to improve low-input cropping practices ( 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…23 There is need to apply strategies to reduce use of pesticides for food productions such as promotion of low-efficiency pesticides, use of traceability labels, reliance on other crop protection services like GAPs and mechanical sowing / transplanting. 24,25 Consumer expressed that their health is at risk citing chronic exposure to pesticide residues and consequent health effects like reproductive defects, NCDs like cancer, hypertension, diabetes, obesity, kidney and liver disease were the major effects. Our findings correlate with findings from previous studies in Africa and German which found that consumers rated pesticide residue contaminants as a serious threat to their health, 8,9,[26][27][28] in fact, Kher and colleagues found that consumers were specifically concerned about health risks that were likely to result from their long term exposure to these chemicals.…”
Section: Discussionmentioning
confidence: 99%
“… 23 There is need to apply strategies to reduce use of pesticides for food productions such as promotion of low-efficiency pesticides, use of traceability labels, reliance on other crop protection services like GAPs and mechanical sowing / transplanting. 24 , 25 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, AMS can help promote the formation of pro-environmental behaviors among farmers, which in turn improves the AGTFP at the micro level [ 44 ]. However, it has also been pointed out that AMS enhances the use of abandoned or poorly managed arable land, thereby increasing the intensity of environmental factor inputs such as pesticides [ 62 ].…”
Section: Literature Reviews and Theoretical Frameworkmentioning
confidence: 99%